2022
DOI: 10.3390/md20080524
|View full text |Cite
|
Sign up to set email alerts
|

Archaea Carotenoids: Natural Pigments with Unexplored Innovative Potential

Abstract: For more than 40 years, marine microorganisms have raised great interest because of their major ecological function and their numerous applications for biotechnology and pharmacology. Particularly, Archaea represent a resource of great potential for the identification of new metabolites because of their adaptation to extreme environmental conditions and their original metabolic pathways, allowing the synthesis of unique biomolecules. Studies on archaeal carotenoids are still relatively scarce and only a few wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 161 publications
0
14
0
Order By: Relevance
“…Carotenoids play a key role in the processes of photoprotection (Grivard et al 2022) and are found to be important in protecting against UV-C radiation in H. salinarium by scavenging for hydroxyl radicals (Kottemann et al 2005;Shahmohammadi et al 1998). It was found that the N. altunense 4.1R genome encodes carotenoid biosynthesis enzymes, including phytoene synthase (crtB) isopentenylcarotenoid (crtD), lycopene beta-cyclase (crtY), phytoene desaturase (crtI) and beta-carotene family in addition to genes involved in bacterioruberin biosynthesis like lycopene elongase and bisanhydrobacterioruberin hydratase like reported in several other haloarchaea (Kottemann et al 2005;Shahmohammadi et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids play a key role in the processes of photoprotection (Grivard et al 2022) and are found to be important in protecting against UV-C radiation in H. salinarium by scavenging for hydroxyl radicals (Kottemann et al 2005;Shahmohammadi et al 1998). It was found that the N. altunense 4.1R genome encodes carotenoid biosynthesis enzymes, including phytoene synthase (crtB) isopentenylcarotenoid (crtD), lycopene beta-cyclase (crtY), phytoene desaturase (crtI) and beta-carotene family in addition to genes involved in bacterioruberin biosynthesis like lycopene elongase and bisanhydrobacterioruberin hydratase like reported in several other haloarchaea (Kottemann et al 2005;Shahmohammadi et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, antioxidant supplementation provides adjuvant tool to fight viral infection and pathological complication [ 38 , 39 ]. It is known that carotenoids attenuate oxidative stress and regulate the overactivation of inflammatory cytokines and proinflammatory enzymes, which are caused by viral infection [ 11 , 12 ]. Supplementation of natural Sur exhibited potent antioxidant and anti-inflammatory activities and showed improvement in lung function and in numerous lung diseases (pneumonia and asthma) [ 12 , 13 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…M6 (source of these active extracts) is environmentally friendly and cost-effective microorganism that can adapt to a harsh hypersaline environment, producing numerous active metabolites including, a unique Sur agent and a rare Pig containing four hydroxyl groups (C50 bacterioruberin) [ 8 , 9 ]. This carotenoid pigment has numerous health benefits, including anticancer, inhibition of viral replication [ 8 ], and prevention of COVID 19 complications (uncontrolled proinflammatory cytokine storm and dysregulating renin-angiotensin system) [ 10 , 11 ]. Regarding natural biosurfactant, it is more effective than its synthetic counterpart in the term of decreasing ARDS complications.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of carotenoids (also termed "carotenogenesis") and its regulation have not been studied as deeply in haloarchaea [26,[41][42][43][44] as they have in bacteria, yeasts, or plants [27,[45][46][47][48][49][50][51][52]. In brief, haloarchaea use the mevalonate pathway to produce the carotenoid precursor isopentenyl pyrophosphate.…”
Section: Carotenogenesis and Biological Role Of Carotenoids In Haloar...mentioning
confidence: 99%